The Mode of Leadership in a Traditional Islamic Boarding School - Muhaemin Muhaemin (JICSA : Journal of Islamic Civilization in Southeast Asian, 2014)
The intent of this study is to elaborate the mode of leadership in a traditional Islamic Boarding School (pesantren) and explore in detail how types of leadership sustain the existence of pesantren in light of globalization of education. This study relies on qualitative research through conducting personal communication with the leaders in the pesantren as well as examining the literature which support the central theme. The research will focus on pesantren Mangkoso Barru, Indonesia. It represents a traditional pesantren in the region of South Sulawesi. The data will be collected from the staff from this particular pesantren. It will be analyzed systematically. The findings suggest that there are, at least, two leadership styles found in the pesantren, charismatic and transformational leadership. The first one basically takes place among the top leaders (senior kiais) of the pesantren while transformational leadership occurs in the middle leaders (junior kiais) of the pesantren. Both leadership styles strongly affect the sustainability of pesantren in the face of globalization of education. Moreover, the leaders of the pesantren are able to transform pesantren values into modernity which enables the pesantren DDI Mangkoso to sustain itself amid the fast wave of modernization.